A crystal plasticity FE study of macro- and micro-subdivision in aluminium single crystals 001<110> multi-pass rolled to a high reduction. (20th June 2021) - Wang, Hui; Lu, Cheng; Tieu, Kiet; Liu, Yu
Abstract: In this study, the substructure formation in a multi-pass rolled aluminium single crystal 001<110> was investigated by the crystal plasticity finite element model, and the predations were validated by experimental observations at both macro- and micro-scale. A finite element model for multi-pass rolling was developed to follow the real experimental rolling scheme, by which the through-thickness macroscopic subdivision was successfully predicted up to a 90 % reduction. The macro-subdivision was featured by forming matrix bands through the thickness, and the deformation behaviours, in terms of slip activity, shear strain and crystal rotation, alternated between matrix bands. The development of matrix bands, stability of crystal orientations, and correlation between slip activity, shear strain and crystal rotation have been investigated. Another modelling method, Submodel, was used to exceedingly increase the mesh resolution in smaller regions of interest, and the experimentally observed microstructure, i.e., micro-subdivision was explicitly and spatially revealed. Similar predictions were obtained in Submodels with different element sizes, which proves the feasibility of this method in predicting microstructure formation. It was found that the substructure formation by varying slip activity and crystal rotation between domains is energy favourable. The procedure of substructure formation was explained based on the predictions, three types of substructure have been identified, and the substructure formation was discussed.